The Energy Independence of the Baltic States: Influence of Geopolitics on Economy - M. F. Kasems (Проблемы постсоветского пространства, 2017)
One of the present-day aims of Baltic countries is to get rid of energy independence from Russia. The situation in Baltic region after the Soviet Union collapse has its negative impact on Baltic’s economy. In the article it could be found the roots of an attempt to create an energy independence from Russia and the research reflects the irrationality of such approach. The geopolitical causes shall be analyzed as well.